THE EFFECT OF TOP EXECUTIVES' EXPERTISE AND BUSYNESS ON EARNINGS MANAGEMENT OF PROPERTY, REAL ESTATE, WHOLESALE, AND RETAIL TRADE COMPANIES IN INDONESIA - Isna Putri Rahmawati (Universitas Airlangga, 2023)
This study aims to empirically prove the effect of top executives' characteristics toward earnings management in the sub-sector of property, real estate, wholesale, and retail trade companies listed on the IDX from 2018 to 2019. The top executives' characteristics are proxied by their expertise and busyness measured by accounting and financial formal educational background the as well as interlocking directorship. The absolute value of discretionary accruals was used to measure the earnings management. Meanwhile, 220 observations were obtained through a purposive sampling technique. The results showed that top executive expertise is negatively related to earnings management. The control variables, company size, and family ownership negatively affected earnings management; however, audit quality has no significant relationship.